Critical Care - Vincent, Jean-Louis.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Critical Care is a high-quality, peer-reviewed, international clinical medical journal. Critical Care aims to improve the care of critically ill patients by acquiring, discussing, distributing, and promoting evidence-based information relevant to intensivists. Critical Care aims to provide a comprehensive overview of the intensive care field.
Keywords: Medicine; Emergency medicine; Critical care medicine; Medicine & Public Health; Intensive / Critical Care Medicine; Emergency Medicine